Evaluation of the electrical conductivity of forest seeds after digestive tract of wild birds - Thode Filho, Sérgio; Franco, Heider Alves; Jorge, Emanuele Nunes de Lima Figueiredo; Fernandes, Miqueias da Silva; Ferreira, Ildemar; Berto, Bruno Pereira (Ciência e Natura, 2018)
The production of seedlings encompasses the need for knowledge of plant physiology, mainly related to seeds and their minutiae. The seed is the vehicle that carries the full genetic potential of a cultivar with superior characteristics. Vigor can be described as that seed property that determines its emergence under unfavorable conditions. According to the International Seed Testing Association (ISTA). The process of reforestation can happen through the production of seedlings and, through seed dispersal, this can occur due to the action of the plant itself (autochory), water (hydrochory), wind (anemochory), animals (zoochory), etc. The current work aimed to investigate the feasibility of using the individual electrical conductivity test to evaluate the physiological quality of seeds of forest species after passage through the digestive tract of wild birds. The results allowed inferring that the forest seeds after digestive tract of wild birds presented low electrical conductivity at the individual level. Thus, the seeds in study no presented loss force after digestive tract of wild birds. Therefore, the birds only performed the role of individual dispersant.